Is the DeVries-Rose to Weber Transition Empirically Possible with Sine-Wave Gratings? - García-pérez, Miguel A. (The Spanish Journal of Psychology, 2005)
Visual functioning at various retinal illuminance levels is usually measured either by determining grating acuity as a function of light level or by determining how sensitivity to sine-wave gratings changes with retinal illuminance. The former line of research has shown that grating acuity follows a two-branch relationship with retinal illuminance, with the point of discontinuity occurring at the transition from scotopic to photopic vision. Results of the latter line of research have summarily been described as a transition from the DeVries-Rose law to Weber’s law, according to which log sensitivity increases linearly with log illuminance with a slope of 0.5 over a range of low illuminances (the DeVries-Rose range) and then levels off and does not increase with further increases of illuminance (the Weber range). This paper aims at determining the compatibility of the results of these two lines of research. We consider empirical constraints from data bearing on the shape of the surface describing contrast sensitivity to sine-wave gratings as a function of spatial frequency and illuminance simultaneously, in order to determine whether they are consistent with a summary description in terms of DeVries-Rose and Weber’s laws. Our analysis indicates that, with sine-wave gratings, the DeVries-Rose law can only hold empirically at low spatial frequencies.